Franglais : la marque de fabrique de la presse à scandale française - Elodie Martin (Corela)
This article aims to develop how and why Franglais, which is, as a general rule, condemned, is used in French tabloids, which also receive bad reviews. Thanks to a corpus composed of headlines, article titles, and excerpts from articles coming from the online French tabloids Closer, Gala, Grazia, Paris Match, Public, Purepeople, and Voici, we start our analysis with a first part devoted to the specific features of Franglais applied to French tabloids, that is to say the codified and targeted aspects of this lexicon as well as the notion of “quantity”. Then, in a second part, we deal with the main reasons explaining the use of Franglais in this kind of press by tackling the following key notions : “linguistic economy” (Martinet 1955) and “in-group identity” (Brown and Levinson 1987).